Analisis Bahan Ajar Anatomi Fisiologi Tubuh Manusia (Karya Daniel Suranta Ginting, Et Al) - Waruwu, Sela Marselina; Zega, Listen Arahan; Harefa, Lindawati; Ndraha, Fita Kristiani; Lase, Natalia Kristiani (Indo-MathEdu Intellectuals Journal, 2024)
In the world of education, teaching materials have a crucial role in the teaching and learning process. Teaching materials include all types of materials used by teachers or instructors to support learning activities in the classroom. Thus, teaching materials are prepared to achieve the desired goals, namely mastering the necessary competencies or subcompetencies along with all their aspects. The purpose of this study is to analyze the identity, content and advantages and disadvantages of a teaching material. The method used in this study is the research method of the pustka study. The results of this study are teaching materials on Physiological Anatomy of the Human Body" by Daniel Suranta Ginting, et al, presenting material about the working system of human body organs and explaining the basics of physiological anatomy and metabolic processes of the human body. This book summarizes eleven discussion materials about the organ system of the human body from the musculelenal, endocrine, lymphatic, urinary, reproductive, respiratory, digestive, and metabolic systems of the human body. This teaching material is written by eleven writers from various professional backgrounds and is compiled in collaboration and cooperation from various authors.